2021
DOI: 10.1093/eurheartj/ehab724.2952
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of cardiovascular outcome trials assessing the impact of glucagon-like peptide-1 receptor agonists on major cardiac arrhythmias

Abstract: Background Type 2 diabetes mellitus poses a significant health burden, whereas growing attention has been focused on the novel classes of antidiabetic drugs. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) constitute such a group of antidiabetic agents. In recent large, placebo-controlled randomized clinical trials (RCTs), GLP-1RAs have demonstrated beneficial cardiovascular effects. Nevertheless, the clear antiarrhythmic benefit has not been underlined yet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The risks of arrhythmias and their subtypes in published high-quality CVOTs of GLP-1RA drug therapy in patients with type 2 diabetes up to March 1, 2022, were therefore extracted, based on this, we also conducted a systematic review and meta-analysis. The novelty of this study is that we included the most recent AMPLITUDE-O trial, which were not included in the 2021 meta-analysis ( 9 ), and we also looked at the risk of hypoglycemia and pneumonia. We included a sample of 60,081 participants from 8 CVOT trials, of which 46,100 had a history of cardiovascular disease (76.7%), and showed that GLP-1RA had no effect on the risk of total arrhythmias [RR=0.96, 95% CI (0.96, 1.05), p =0.36] in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risks of arrhythmias and their subtypes in published high-quality CVOTs of GLP-1RA drug therapy in patients with type 2 diabetes up to March 1, 2022, were therefore extracted, based on this, we also conducted a systematic review and meta-analysis. The novelty of this study is that we included the most recent AMPLITUDE-O trial, which were not included in the 2021 meta-analysis ( 9 ), and we also looked at the risk of hypoglycemia and pneumonia. We included a sample of 60,081 participants from 8 CVOT trials, of which 46,100 had a history of cardiovascular disease (76.7%), and showed that GLP-1RA had no effect on the risk of total arrhythmias [RR=0.96, 95% CI (0.96, 1.05), p =0.36] in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 meta-analysis showed that exenatide was associated with an increased risk of arrhythmias in type 2 diabetes (OR 2.83; 95% CI: 1.06-7.57) ( 8 ). In 2021 another linked meta-analysis showed that in type 2 diabetic patients, using GLP-1RA treatment did not significantly affect the risk of major arrhythmia ( 9 ). Thus, it is clear that the controversial findings of before-and-after studies for arrhythmias and the few studies investigating the effect of GLP-1RA on the outcome of different arrhythmia subtypes, together with the recent publication of new RCTs on GLP-1RA on CVD outcome.…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis included 27 randomized controlled trials (RCTs), of which most used MI as an exclusion criterion, i.e., did not include the T2DM people combined with MI ( 11 ). In another meta-analysis, although all seven RCTs included patients with MI, the proportions varied considerably, e.g., 82.6% of such patients in the ELIXA study but only 16.2% in the REWIND study ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, some studies reported their neutral relationship. Both Al-Sadawi et al’s ( 11 ) and Boulmpou et al’s ( 12 ) meta-analyses indicated that treatment with GLP-1RAs does not significantly affect the risk for atrial or ventricular arrhythmias.…”
Section: Introductionmentioning
confidence: 99%